Homogeneous nucleation of carbon dioxide in supersonic nozzles II: molecular dynamics simulations and properties of nucleating clusters. Issue 8 (17th February 2021) - Halonen, Roope; Tikkanen, Valtteri; Reischl, Bernhard; Dingilian, Kayane K.; Wyslouzil, Barbara E.; Vehkamäki, Hanna
Abstract : Molecular dynamics simulations reveal the structural and energetic properties of carbon dioxide clusters nucleating in the gas phase at extreme undercooling. Abstract : Large scale molecular dynamics simulations of the homogeneous nucleation of carbon dioxide in an argon atmosphere were carried out at temperatures between 75 and 105 K. Extensive analyses of the nucleating clusters' structural and energetic properties were performed to quantify these details for the supersonic nozzle experiments described in the first part of this series [Dingilian et al., Phys. Chem. Chem. Phys., 2020, 22, 19282–19298]. We studied ten different combinations of temperature and vapour pressure, leading to nucleation rates of 10 23 –10 25 cm −3 s −1 . Nucleating clusters possess significant excess energy from monomer capture, and the observed cluster temperatures during nucleation – on both sides of the critical cluster size – are higher than that of the carrier gas. Despite strong undercooling with respect to the triple point, most clusters are clearly liquid-like during the nucleation stage. Only at the lowest simulation temperatures and vapour densities, clusters containing over 100 molecules are able to undergo a second phase transition to a crystalline solid. The formation free energies retrieved from the molecular dynamics simulations were used to improve the classical nucleation theory by introducing a Tolman-like term into the classical liquid-drop model expression for the formation free energy. This simulation-based theory predicts the simulated nucleation rates perfectly, and improves the prediction of the experimental rates compared to self-consistent classical nucleation theory.